Single denture as a treatment for a patient with TMD: a case report - Andi, Adytha Mutiah; Arsista, Dede; Aprianto, Dharma Satya; Priambodo, Agung (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: Temporomandibular joint disorder is a chronic pain caused by various factors including trauma, occlusal condition, and stress. This case report will explain about TMD case in prosthodontic which is treated with a single denture. Methods: A 50-year-old woman came to the dental clinic with aches and pains in the jaw and muscles around the head and neck. She has been using a removable denture since two months ago, but she feels uncomfortable with it. We made a new denture with an appropriate vertical dimension for the patient, with the tooth arrangement as close to the compensating curves as possible. We also trained her to do some exercises for the head and neck muscle. Results: After wearing the new denture and doing a series of muscle therapy, the patient begins to feel that the aches and pains are starting to decrease. She can more easily open and close her mouth and her lower jaw no longer feels so vibrating. Conclusion: Based on the results of clinical and subjective examinations, apart from tooth loss, all the conditions experienced by the patient also seem to be related to emotional stress due to the problems encountered.